Comparative Efficacy of Phenytoin Versus Lidocaine in the Management of Intractable Seizure in Neonate (Journal of Dhaka Medical College, 2017)
Background : Intractable neonatal seizure are common acute medical emergency in neonatal period than at any other period of life. In our daily practice treatment of intractable neonatal seizures still relies primarily on phenytoin, despite an estimated efficacy of less than 50% and concern over neurodegenerative side effects. Several studies indicate value for lidocaine as an anticonvulsant in the treatment of intractable neonatal seizure.Aim : The objective of this study was to compare the efficacy of Phenytoin with Lidocaine in the management of intractable seizure in neonate.Methodology : A Randomized control trial was carried out in the Department of Neonatology, Dhaka Medical College Hospital (DMCH), Dhaka between July 2013 to June 2014. A total of 78 newborn with neonatal seizure. admitted in SCABU & not responding to total doses of Inj. Phenobarbital (40 mg/kg) were included in the study and were randomly assigned to either Inj. Lidocaine (Group A=39) or to Inj. Phenytoin (Group B=39). The main outcome variables were control of seizure, adverse effects, time of cessation of seizure.Results : The study demonstrated that intractable seizure of 24 neonates (75%) were controlled with Inj. Lidocaine and intractable seizure of 20 neonates (57.1%) were controlled with Inj. Phenytoin(P-Value 0.124). Adverse effects of drugs such as apnea, bradycardia, drowsiness and lethargy were observed in 4 patients (12.5%) of Lidocaine group (Group A) and 10 (28.6%) of Phenytoin group (Group=B) (P-Value 0.106). Time required for cessation of intractable seizures were nearly similar in both groups. In group A 75% of patients responded within 24 hours and in group B 71% patients responded in same duration(P-Value 0.931). Length of hospital stay was less in phenytoin group compare to lidocaine group(P-Value 0.352). None of the following results were statistically significant.Conclusion : The study concluded that Inj. Lidocaine is similar to Inj. Phenytoin in controlling intractable neonatal seizure.J Dhaka Medical College, Vol. 25, No.2, October, 2016, Page 94-99